1997
DOI: 10.1144/gsl.sp.1997.124.01.14
|View full text |Cite
|
Sign up to set email alerts
|

The presence of sulphate-reducing bacteria in live drilling muds, core materials and reservoir formation brine from new oilfields

Abstract: The sulphate-reducing bacteria (SRB) produce the toxic gas hydrogen sulphide (H2S) and cause numerous problems in the oil and gas industry. It has been suggested that these organisms are either introduced to the formation by drilling or water injection or that they may be indigenous. Little is known of the activity and survival mechanisms of the SRB under reservoir conditions. In this study a number of samples from hydrocarbon reservoirs were inoculated into sulphate-rich growth medium to determine the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Microbes or bacteria can trigger oxidation reactions involving loss of hydrogen a result of corrosion, pitting, and stress cracking of downhole and surface equipment [31]. Microbes or bacteria can also trigger the loss of sulphates, ultimately producing hydrogen sulphide gas, which can have adverse health impacts on rig personnel throughout drilling operations; these bacteria are either natives of the reservoir or have been brought into the reservoir during drilling operation [33]. Mcgovern-Traa et al [33] reported that the behaviour of these bacteria under reservoir conditions are not completely understood [33].…”
Section: Biological Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbes or bacteria can trigger oxidation reactions involving loss of hydrogen a result of corrosion, pitting, and stress cracking of downhole and surface equipment [31]. Microbes or bacteria can also trigger the loss of sulphates, ultimately producing hydrogen sulphide gas, which can have adverse health impacts on rig personnel throughout drilling operations; these bacteria are either natives of the reservoir or have been brought into the reservoir during drilling operation [33]. Mcgovern-Traa et al [33] reported that the behaviour of these bacteria under reservoir conditions are not completely understood [33].…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Microbes or bacteria can also trigger the loss of sulphates, ultimately producing hydrogen sulphide gas, which can have adverse health impacts on rig personnel throughout drilling operations; these bacteria are either natives of the reservoir or have been brought into the reservoir during drilling operation [33]. Mcgovern-Traa et al [33] reported that the behaviour of these bacteria under reservoir conditions are not completely understood [33]. However, if these sulphatereducing bacteria (SRB) are indigenous and feed on nutrients contained in reservoir drilling fluid (RDF) or injected water, this means that the associated formation damage reactions will extend beyond the near-wellbore region, reaching rather deep into the sandstone reservoir [34].…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Because of being the last addition to the reservoir, treatment of the fracturing fluids represents an appropriate location to apply remediation strategies to help maintain integrity of the future well and minimizing production of sour oil or gas. Additionally, the drilling process is another possible source of contamination in the wellbore because drilling muds are circulated through thousands of feet of subterranean formations while being recycled into an open tank or pit (Mcgovern-Traa et al 1997;Struchtemeyer et al 2011). Regardless, when microbes are introduced, adequate treatment is necessary to mitigate the possibility that these detrimental bacteria establish viable colonies in the wellbore and in the formation (Johnson et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of microbes in oilfield reservoirs is widely accepted, and have been isolated from oilfield reservoirs world wide (1 & 2). These microbes while often native to the reservoirs can also be introduced as a result of drilling operations and/or water injection (3).…”
Section: Introductionmentioning
confidence: 99%